Speed Flow Density Models Prediction for Urban Roadway in Falluja City - Ahmed Abbas, Rafal; I. Alkubaisi, Mehdi (Anbar Journal of Engineering Sciences, 2011)
This research focuses on studying the speed flow density relationships which are considered the fundamental traffic flow relationships. The objective of the present study is to predict statistical models represent these relationships depending on a field survey data collected from Al-Thirthar road in Falluja city.Data were collected by using video-recording technique. The required data were abstracted, analyzed, grouped, and processed using computer programs developed for this purpose. Standard statistical analysis techniques were used to examine and analyze the observed data.FWASIM simulation traffic software program was used to verify the predicted traffic stream models, while the obtained results were presented in this research. To test the validity and reliability of the model, the output results of the predicated model were compared with the output data obtained from FWASIM model using similar input data and segment geometry. The comparison leads to consider that the developed regression model may be used to evaluate the performance of urban streets in Falluja city.